2018
DOI: 10.1007/s10616-018-0247-z
|View full text |Cite
|
Sign up to set email alerts
|

The anti-angiogenic potential of (±) gossypol in comparison to suramin

Abstract: Cotton, a staple fiber that grows around the seeds of the cotton plants (Gossypium), is produced throughout the world, and its by products, such as cotton fibers, cotton-seed oil, and cottonseed proteins, have a variety of applications. Cotton-seed contains gossypol, a natural phenol compound. (±)-Gossypol is a yellowish polyphenol that is derived from different parts of the cotton plant and contains potent anticancer properties. Tumor growth and metastasis are mainly related to angiogenesis; therefore, anti-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…In recent years, strategies that prevent the feeding or metastasis of tumor cells have become more popular than directly intervening with the tumor in the cancerous tissue [23,24]. The chick chorioallantoic membrane (CAM) assay is a method that quantitatively and visually confirms the anti-or proangiogenic effectiveness of the tested sample [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, strategies that prevent the feeding or metastasis of tumor cells have become more popular than directly intervening with the tumor in the cancerous tissue [23,24]. The chick chorioallantoic membrane (CAM) assay is a method that quantitatively and visually confirms the anti-or proangiogenic effectiveness of the tested sample [25].…”
Section: Resultsmentioning
confidence: 99%
“…Antiangiogenic effects of samples were determined on fertile Leghorn chicken eggs weighing 50-60 g by using a CAM method modified by Ulus et al [25]. Fertilized eggs were placed into an incubator with a conveyor rotation system at 37 ± 1 • C and 80 ± 2% humidity for 6 days.…”
Section: Antiangiogenic Activitymentioning
confidence: 99%
“…Numerous studies have reported that angiogenesis is a hallmark of the malignant transformation of tumors [12, 13]. Several antitumor drugs are aimed at inhibiting neovascularization to reduce the oxygen and nutrient supply of tumors, which prevents the growth of tumors [1416]. ANGPTL2 has been shown to contribute to the proliferation and invasion of gastric cancer cells, and it has been reported to be a potential biomarker for colorectal cancer [17].…”
Section: Discussionmentioning
confidence: 99%
“…Natural products derived from plants have been used as herbal medicines for a long time. Because of the harmful side effects of chemical agents, plants used in medicine have been very popular recently (Ulus et al, 2018). Lichens are symbiotic organisms composed of fungi (mycobiont) and green algae and/or cyanobacteria (photobiont; Emsen et al, 2016;Varol, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Lichen secondary metabolites have important roles in metal balance and protection against pollution in the organism (Molnár & Farkas, 2009). Angiogenesis is the process of the growing of new vessels from pre-existing vessels (Ulus et al, 2018;Figure 2). Angiogenesis which is a complex mechanism is a response to the increasement in requirements of oxygen and nutrient in tissue mass (Tong et al, 2004).…”
Section: Introductionmentioning
confidence: 99%